Risk of Stroke or Heart Attack in Mild Cognitive Impairment and Subjective Cognitive Impairment - Michele Lauriola; Luigi Esposito; Grazia D’Onofrio; Filomena Ciccone; Annamaria la Torre; Filomena Addante; Annagrazia Cocomazzi; Leandro Cascavilla; Olga Ariano; Gaetano Serviddio; Antonio Greco (Neurology International)
Background: The study aimed to identify Mild Cognitive Impairment (MCI) as an alert clinical manifestation of increased probability of major acute vascular events (MVEs), such as Ischemic Stroke and heart attack. Methods: In a longitudinal study, 181 (M = 81, F = 100; mean age of 75.8 ± 8.69 years) patients were enrolled and divided into three groups based on diagnosis: Subjective Cognitive Impairment (SCI), amnestic MCI Single Domain (aMCI-SD), and amnestic MCI More Domain (aMCI-MD). Clinical assessment and the presence of vascular risk factors were collected. Results: The distribution of MVEs showed a higher incidence in the first two years of follow-up of 7.4% in SCI, 12.17% in aMCI-SD, and 8.57% in aMCI-MD. Acute Myocardial Infarction showed a major incidence in one year of follow-up (41%) and in two years of follow-up (29%). Also, Ischemic Stroke showed a major incidence in one year of follow-up (30%) and in two years of follow-up (40%). A statistically significant difference in the progression to dementia was shown (SCI 3.75%; aMCI-SD 10.43%; aMCI-MD 37%; p-value < 0.001). Conclusions: MCI is considered an expression of the systemic activation of mechanisms of endothelial damage, representing a diagnosis predictive of increased risk of MVEs.